Import of several tRNAs from the cytoplasm into the mitochondria in bean Phaseolus vulgaris. - Maréchal-Drouard, L (1988)
Four P. Vulgaris mitochondrial tRNA(Leu) species have been shown to be nuclear encoded. These mt tRNAs(Leu) can be used for in vitro protein synthesis. We found that the sequences of P. vulgaris mitochondrial and cytoplasmic tRNAs(Leu)(NAG) are identical except for a post-transcriptional modification occurring at position 18 (Gm in mt tRNA(Leu) instead of G in cyt tRNA(Leu], as in the case of mt and cyt tRNAs(Leu)(NAA) already sequenced. This post-transcriptional modification has also been found in two other bean mt tRNA(Leu) species, but not in P. vulgaris cytoplasmic tRNA(Leu) species that we have purified so far. Furthermore, comparison of the 2-D polyacrylamide gel electrophoretic patterns of tRNAs eluted from bean mt tRNA-mtDNA and mt tRNA-nDNA hybrids revealed at least 8 mt tRNAs coded for by the nuclear genome.